Politik Tata Ruang dan Eksklusi Masyarakat Lokal : Studi Kasus Alih Fungsi Lahan Hutan Bowosie di Labuan Bajo - Yustinus Kevinsius Fenti; Yonathan H.L.Lopo; Philips Y. N. Ndoda (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
This study analyzes the politics of spatial planning in the land-use conversion of the Bowosie Forest in Labuan Bajo as part of the National Strategic Project (PSN) for tourism development. The transformation of the forest into an economic tourism zone demonstrates that spatial planning is not neutral, but rather an arena of power relations among the state, investors, and local communities. Through regulatory instruments such as revisions of the Regional Spatial Plan (RTRW), ministerial decrees on forest release, and the granting of Management Rights (HPL) to BPOLBF, the state has facilitated tourism investment and the commodification of space. Using a qualitative approach and David Harvey’s theory of Accumulation by Dispossession, the study finds that these policies have produced three forms of exclusion: spatial exclusion (loss of access to land and water sources), political exclusion (limited community participation in decision-making), and economic exclusion (development benefits concentrated among investors). The village government occupies a structurally limited position due to the top-down nature of the policy framework. The study concludes that the conversion of the Bowosie Forest reflects a process of capital accumulation legalized through state regulation, highlighting the need for more inclusive and socially just spatial planning.